2021
DOI: 10.1101/2021.06.10.447951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Potency of COVIran Barekat Inactivated Vaccine Candidate for SARS-CoV-2: A Preclinical Study

Abstract: There is an urgent demand to manufacture an effective and safe vaccine to prevent SARS-CoV2 infection, which resulted in a global pandemic. In this study, we developed an inactivated whole-virus SARS-CoV-2 candidate vaccine named COVIran Barekat. Immunization at two different doses (3 microgram or 5 microgram per dose) elicited a high level of SARS-CoV-2 specific neutralizing antibodies in mice, rabbits, and non-human primates. The results show the safety profile in studied animals (include guinea pig, rabbit,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…CovIran Barekat is an inactivated whole virus vaccine against Sars-Cov-2 manufactured by the Shifapharmed Industrial Group Company in Iran. The animal trial result, published as a preprint, shows that this vaccine can induce an immune response with adequate safety in mice, rabbits, and non-human primates [56]. Study protocols were registered in the Iranian Registry of Clinical trials (IRCT20201202049567N1, IRCT20201202049567N2, and IRCT20201202049567N3).…”
Section: Vaccines Profilementioning
confidence: 99%
“…CovIran Barekat is an inactivated whole virus vaccine against Sars-Cov-2 manufactured by the Shifapharmed Industrial Group Company in Iran. The animal trial result, published as a preprint, shows that this vaccine can induce an immune response with adequate safety in mice, rabbits, and non-human primates [56]. Study protocols were registered in the Iranian Registry of Clinical trials (IRCT20201202049567N1, IRCT20201202049567N2, and IRCT20201202049567N3).…”
Section: Vaccines Profilementioning
confidence: 99%
“…Inactivated SARS-CoV-2 vaccines based on inactivated viruses such as COVIran Barekat may have better efficacy against variants that have mutations in the spike protein. 96 Similar to AstraZeneca, Sinovac, and Sinopharm developed vaccines, COVIran Barekat should be kept at 2-8 º C. It has been reported that this vaccine is about 93% effective in COVID-19 prevention. 97 COVIran Barekat is well tolerated in two doses (5 µg) of intramuscular injection.…”
Section: Coviran Barekatmentioning
confidence: 99%
“…Alum adjuvant was utilized in the formulation of COVIran Barekat to achieve an effective and robust immune response. 45 In phase 1 clinical trial (IRCT20201202049567N1), the vaccine was evaluated on 56 healthy volunteers with the age range of 18–55 years, which led to satisfactory safety and immune response. In the second phase 1 clinical trial (IRCT20201202049567N2), the evaluation of the vaccine was started in a smaller population, that is, 32 healthy adults aged 51–75 years.…”
Section: Coviran Barekat Vaccinementioning
confidence: 99%
“…SARS‐CoV‐2 virus culture on Vero monolayers cells and then virus particles were inactivated using PBL. Alum adjuvant was utilized in the formulation of COVIran Barekat to achieve an effective and robust immune response 45 . In phase 1 clinical trial (IRCT20201202049567N1), the vaccine was evaluated on 56 healthy volunteers with the age range of 18–55 years, which led to satisfactory safety and immune response.…”
Section: Coviran Barekat Vaccinementioning
confidence: 99%